2006
DOI: 10.1111/j.1365-2672.2006.03008.x
|View full text |Cite
|
Sign up to set email alerts
|

Composting is an effective treatment option for sanitization of Phytophthora ramorum-infected plant material

Abstract: Aims:  To determine the effects of heat and composting treatments on the viability of the plant pathogen Phytophthora ramorum grown on both artificial and various natural substrates. Methods and Results:  Phytophthora ramorum was grown on V8 agar, inoculated on bay laurel leaves (Umbellularia californica) and on woody tissues of coast live oak (Quercus agrifolia). Effects on growth, viability and survival were measured as a result of treatment in ovens and compost piles. Direct plating onto PARP medium and pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…There have been early reports of the ability of P. ramorum to grow over a wide range of temperatures (Werres et al, 2001;Harnik et al, 2004;Swain et al, 2006). This is confirmed by an experimental study of P. ramorum infection (using the NA1 isolate) of Cunningham's White Rhododendron, with P. ramorum able to infect this host over a wide range of temperatures and moisture levels Similar results are obtained from a study of the susceptibility to P. ramorum and sporulation potential of 25 understory plant species growing in Eastern North America .…”
Section: Additional Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…There have been early reports of the ability of P. ramorum to grow over a wide range of temperatures (Werres et al, 2001;Harnik et al, 2004;Swain et al, 2006). This is confirmed by an experimental study of P. ramorum infection (using the NA1 isolate) of Cunningham's White Rhododendron, with P. ramorum able to infect this host over a wide range of temperatures and moisture levels Similar results are obtained from a study of the susceptibility to P. ramorum and sporulation potential of 25 understory plant species growing in Eastern North America .…”
Section: Additional Informationmentioning
confidence: 99%
“…RAPRA already identifies some potential sporulating hosts, however no clear discussion is provided on how to effectively deal with infected plant material. Two papers have addressed sanitation in California: one dealt with the ability of heat and heat vacuum treatments to reduce viability of foliar infection to zero (Harnik et al, 2004), while a second paper showed that composting following EPA guidelines successfully eliminates all traces of P. ramorum, even in cases where massive infection of foliage was tested (Swain et al, 2006). Risk when moving infected plant parts needs to be considered and it could be mitigated by adopting these proved techniques or investigating alternative approaches.…”
Section: Options To Reduce Infestation and Magnitude Of Impact In Thementioning
confidence: 99%
See 2 more Smart Citations
“…The composting process can eradicate even the toughest resting propagules commonly produced by P. ramorum if the process is conducted according to U.S. Environmental Protection Agency (EPA) PFRP guidelines (Swain et al 2006).…”
mentioning
confidence: 99%